Bibliography on social justice: sources on the topic in Library and Information Science - Garcês da Silva, Franciéle Carneiro; Garcez, Dirnéle Carneiro; Vieira, Gabriel de Melo; Fevrier, Priscila Rufino; Alves, Ana Paula Meneses [UNESP] (IBICT, 2023)
This research aimed to compile a selective bibliography on social justice in Library Science and Information Science from 1960 to 2020. To that end, the study conducts bibliographic, descriptive, and qualitative-quantitative research using the classification concepts proposed by Dias and Pires (2005) to locate documents in national and international databases on social justice in Library Science and Information Science. After refining the data, the results were presented in a bibliography, in the form of a selective list of documents, with signal presentation, international coverage, specialized subject, retrospective focus, alphabetical and systematic arrangement, divided into three categories: education for social justice, libraries for social justice, and librarian practice aimed at social justice.
Bibliografía sobre justicia social: fuentes sobre el tema en Biblioteconomía y Documentación
Bibliografia sobre Justiça Social: fontes acerca tema em Biblioteconomia e Ciência da Informação
Keywords: bibliography; library and information science; scientific production; social justice